Impacts Of Cyber Security In Iot-Based Cloud Computing. - Gadhavi, Lataben J.; Vaghasia, Madhuri V. (Journal of Namibian Studies)
Cloud computing contributes the elastic and extensible architecture in which resources and data are scattered at different regions and accessible from anywhere. Cloud computing indicates applications and services to implement on a distributed computing network by applying virtualized resources. Meanwhile, industries have rapidly adopted cloud computing technology for secure and effective accessibility, improvement of performance and cost reduction. Moreover, incorporation of cloud computing and internet of things (IoT) has been enhancing in last decade. Hence, this expeditious evolution in the cloud computing technology raised numerous security issues and challenges. IoT with cloud demands exclusive security aspects to overcome the traditional security challenges.Technological advancements like smart cities and IoT needs protected cloud infrastructure to deploy secure system. The conclusion of the research paper comprise a comprehensive survey of facilitating cloudbased architecture of IoT, security models and classification of cloud security with IoT. To blend security in cloud computing, technological challenges and significant research gaps will be considered to highlight future research directions. This chapter presents security and privacy challenges with IoT-based cloud systems.